A taste for fruit: first record of Rekoa marius (Lucas, 1857) (Lepidoptera: Lycaenidae: Eumaeini) on Averrhoa carambola L. (Oxalidales: Oxalidaceae) - Suianne Cajé; Jefferson Duarte-de-Mélo; Ayane Suênia-Bastos; Iracilda Maria de Moura Lima (Revista Chilena de Entomología)
Information on the natural history of Rekoa marius (Lucas, 1857) is presented through the first record of the species on Averrhoa carambola L. The larvae of this lepidopteran were collected on A. carambola and reared under laboratory conditions. Eggs were found on the flower bud, inflorescence and peduncle near the flower. All larval stages feed on flower buds, while the last larval stage also feeds on green and ripe fruits. Pupae with egress holes of different diameters were found, probably of parasitoids. Since Oxalidaceae species are rich in oxalic acid, R. marius may be a potential model for future studies on the mechanisms involved in the response of this species to oxalic acid present in its host plant.